Pengaruh Transparansi, Akuntabilitas, dan Responsivitas Dana Desa Terhadap Pemerintahan Desa: Studi Kasus di Kecamatan Ngunut - Ferlian Aca; Anwar Made; Dimas Emha Amir Fikri Anas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This resears aims to analyze the influence of transparency, accountability, and responsiveness of village funds on the performance of village governance. The main theory used in this research is Stewardship Theory, which states the existence of local administration as one of the trusted institutions in accordance with its obligations and functions. The research method employes is a quantitative approach using data collection thechniques through questionnaires filled out by village heads, village secretaries, treasurers, and heads of service sections. The collected data is numerical and is processed using the Smart PLS application. The results of this study show that transparency and accountability have a significant effect on the performance of village governance, while responsiveness does not have an effect on the performance of village governance.